Influence of FeCl3 and H2O2 in corrosion testing of modular taper connections in total hip arthroplasty: an in vitro study - Bormann, Therese; Nebel, Laura; Müller, Ulrike; Mai, Phuong Thao; Gibmeier, Jens; Renkawitz, Tobias; Kretzer, Jan Philippe (Acta biomaterialia, 2022)
Corrosion at the modular taper junctions in total hip arthroplasty is clinically relevant because wear particles and ions generated at this interface can lead to adverse local tissue reactions or even implant failure. In vitro tribo-corrosion tests are usually accomplished in saline solutions or calf serum (CS), but the addition of H2O2 and FeCl3 have been suggested to mimic inflammatory conditions in the joint. Inflammatory conditions may aggravate corrosive processes and, therefore, should lead in vitro to a more severe and realistic tribo-corrosive material attack. Corrosion testing at 12/14 tapers comprising a CoCrMo head taper and a Ti6Al4V trunnion was accomplished in five electrolytes (Ringer's solution (RS), RS with 30 mM H2O2 and/or 0.7 mM FeCl3 and CS) under dynamical loading for five million cycles. Resulting material loss was determined gravimetrically and by ion analysis. The tribo-corrosive material degradation was investigated by light and electron microscopy. FeCl3 enhanced the material loss from taper connections while H2O2 did not lead to a significant alteration of total material loss. In comparison to pure RS, corrosion testing in CS decreased material loss at the head taper while it increased material loss at the trunnion. The combination of FeCl3 and H2O2 led to an enhanced occurrence of micro cracks at the trunnion surface. Adding FeCl3 and optionally also H2O2 aggravates material loss in in vitro corrosion testing of taper junctions and leads to harsher and probably more realistic testing conditions. - Statement of significance - Tribo-corrosive processes at taper connections in hip implants are complex and can lead to major clinical implications. Joint inflammation is assumed to aggravate taper corrosion in vivo, why FeCl3 and H2O2 have been proposed as additives to electrolytes to simulate inflammatory conditions in vitro. Often used fretting test setups, however, do not involve real taper geometries. Besides, testing is often accomplished in saline solutions or calf serum, which do not induce a clinically significant amount of corrosive material degradation. This study presents an approach to increase tribo-corrosive processes at realistic taper connections by adding FeCl3 and/or H2O2. Unlike H2O2, FeCl3 increased material loss from taper connections. The combination of both additives enhanced micro crack formation at the trunnion surfaces.
Im Titel sind die Zahlen 3 und 2 jeweils tiefgestellt
Gesehen am 14.04.2022